2015
DOI: 10.1097/prs.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Biofilm Infection in Breast Implants Is Associated with an Increased T-Cell Lymphocytic Infiltrate

Abstract: Risk, V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
171
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(180 citation statements)
references
References 27 publications
5
171
0
4
Order By: Relevance
“…19 One model of BIA-ALCL pathogenesis hypothesizes the stimulation of malignant lymphocyte clones by chronic inflammation induced by either the implant contents or its surface characteristics/biofilm. [20][21][22][23] The observation of variants leading to aberrant STAT3 activation in our cases is consistent with this model. Of note, the presence of JAK/STAT3 activating variants in our cases were compatible with prolonged remission when treated with local therapy alone (surgery +/-radiotherapy without systemic chemotherapy), which suggests that additional modifying disease factors (genetic or otherwise) are present in "typical" ALK-negative sALCL in order to give rise to the markedly inferior outcomes observed.…”
supporting
confidence: 77%
“…19 One model of BIA-ALCL pathogenesis hypothesizes the stimulation of malignant lymphocyte clones by chronic inflammation induced by either the implant contents or its surface characteristics/biofilm. [20][21][22][23] The observation of variants leading to aberrant STAT3 activation in our cases is consistent with this model. Of note, the presence of JAK/STAT3 activating variants in our cases were compatible with prolonged remission when treated with local therapy alone (surgery +/-radiotherapy without systemic chemotherapy), which suggests that additional modifying disease factors (genetic or otherwise) are present in "typical" ALK-negative sALCL in order to give rise to the markedly inferior outcomes observed.…”
supporting
confidence: 77%
“…An experimental model in pigs was presented by Hu and colleagues in 2015 (14), showing that capsular contracture Baker grade is directly linked to the number of bacteria for increasing and a threshold of bacterial biofilm exists above which host responses lead to capsular contracture, due to an inflammatory response leading to fibrosis.…”
Section: Complications In Breast Augmentationmentioning
confidence: 99%
“…The immune system's response to chronic inflammation surrounding the breast implant in a genetically susceptible patient, may lead to genetic degeneration and dysplasia (25). In a recent study by Hu et al, the authors compared the implant capsules of patients with BI-ALCL to those with normal capsular contracture, finding a high bacterial load and significantly different microbiome in the BI-ALCL specimens with a high predominance of the bacteria Ralstonia pickettii, a gram-negative rod and common contaminant of drinking water (26). Previous work comparing the capsules of textured and smooth implants in pigs showed that there are increased lymphocytes on textured breast implants, with a T-cell predominance, further supporting texturing as a link to chronic inflammation and T-cell response.…”
Section: Etiology Of Bi-alclmentioning
confidence: 99%